2022
DOI: 10.1055/s-0042-1742722
|View full text |Cite
|
Sign up to set email alerts
|

Neurodevelopmental Outcomes of Neonatal Rotavirus-Associated Leukoencephalopathy

Abstract: Rotavirus infection has been reported to be associated with neonatal seizures with a diffuse and symmetrical diffusion restriction of periventricular white matter, namely, neonatal rotavirus-associated leukoencephalopathy. The extensive white matter injury seen in this cohort raises concerns about the long-term neurodevelopmental outcomes. In the present study, we prospectively assessed the neurodevelopmental outcomes of 13 patients with neonatal rotavirus-associated leukoencephalopathy at a median age of 26 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Our results support previous studies linking rotavirus-induced autoimmunity to arthritis, vasculitis, and neurologic diseases. 31 , 32 Previous studies indicated that rotavirus infection could potentially trigger autoimmunity in immune-privileged sites, 2 including the intestine, 3 , 6 pancreas, 12 , 33 brain, 12 , 13 , 14 , 26 , 32 kidney, 30 and lymph nodes. 29 , 34 Furthermore, animal studies demonstrated that rotavirus can penetrate host cells and replicate in nonenterocytes, possibly evading immune responses and systemic sequelae, 35 indicating potential associations with conditions like type 1 diabetes, 36 vasculitis, 37 and neurologic disorders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our results support previous studies linking rotavirus-induced autoimmunity to arthritis, vasculitis, and neurologic diseases. 31 , 32 Previous studies indicated that rotavirus infection could potentially trigger autoimmunity in immune-privileged sites, 2 including the intestine, 3 , 6 pancreas, 12 , 33 brain, 12 , 13 , 14 , 26 , 32 kidney, 30 and lymph nodes. 29 , 34 Furthermore, animal studies demonstrated that rotavirus can penetrate host cells and replicate in nonenterocytes, possibly evading immune responses and systemic sequelae, 35 indicating potential associations with conditions like type 1 diabetes, 36 vasculitis, 37 and neurologic disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Vaccinations have reduced the prevalence of rotavirus disease, but postinfection illnesses persist. There is also evidence linking rotavirus infection to autoimmune diseases, such as celiac disease, type 1 diabetes, pancreatitis, and neuropathy . However, previous studies had limitations in terms of controls, small sample sizes, and study design .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations